2014
DOI: 10.1016/j.ijdrr.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Seismic and wind vulnerability assessment for the GAR-13 global risk assessment

Abstract: A general methodology to evaluate vulnerability functions suitable for a probabilistic global risk assessment is proposed. The methodology is partially based in the methodological approach of the Multihazard Loss Estimation Methodology (Hazus) developed by the Federal Emergency Management Agency (FEMA). The vulnerability assessment process considers the resolution, information and limitations established for both the hazard and exposure models adopted. Seismic and wind vulnerability functions are estimated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Impact functions for the assessment of direct economic damage caused by TCs usually relate wind speed to relative damage (Emanuel, 2011). For the USA, TC impact functions are available specific to different building types (Federal Emergency Management Authority [FEMA], 2010;Yamin et al, 2014), as well as on an aggregate level (Emanuel, 2011). found a lack of sensitivity of simulated TC 55 damage to the exact shape of the impact function for the USA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Impact functions for the assessment of direct economic damage caused by TCs usually relate wind speed to relative damage (Emanuel, 2011). For the USA, TC impact functions are available specific to different building types (Federal Emergency Management Authority [FEMA], 2010;Yamin et al, 2014), as well as on an aggregate level (Emanuel, 2011). found a lack of sensitivity of simulated TC 55 damage to the exact shape of the impact function for the USA.…”
mentioning
confidence: 99%
“…found a lack of sensitivity of simulated TC 55 damage to the exact shape of the impact function for the USA. However, due to global heterogeneities in the tropical cyclone climatology (Schreck et al, 2014), building codes, and other socioeconomic vulnerability factors (Yamin et al, 2014), one universal impact function might be inappropriate for global TC risk assessments. Bakkensen et al (2018b) used reported damage data to calibrate TC impact functions for China, highlighting both the potential of this approach and the considerable uncertainties related to the quality of reported damage data.…”
mentioning
confidence: 99%
“…Exposure is represented using the common dataset of the GAR 2015, in which it is represented as a group of buildings in each point or cell of analysis with a resolution of 5 km × 5 km. Vulnerability is represented by IDFs relating maximum wind velocity sustained for 5 s gusts at 10 m above ground level (Yamin et al, 2014). Since the results are only for current conditions, future DRR measures are not included.…”
Section: Tropical Cyclonesmentioning
confidence: 99%
“…Their primary output is in map form, with the most elevated impacts found in many of the same locations as in the study of Nadim et al (2004Nadim et al ( , 2006, although they find higher impacts in terms of total GDP in China. Yang et al (2015) assess risk in terms of fatalities for the current period at a resolution of 0.25…”
Section: Landslidesmentioning
confidence: 99%
“…This research uses a total of 35 vulnerability functions (see Table 2 and Figure 5) developed in previous projects conducted by Universidad de los Andes for the World Bank. 47,48 The characterization of the physical vulnerability entails the definition of the relationship between the damage level and the seismic intensity (SI). The damage is represented in terms of the mean damage ratio (MDR), and by its corresponding standard deviation.…”
Section: Vulnerability Functionsmentioning
confidence: 99%